Learning teaching : the essential guide to English language teaching - Scrivener, Jim. (UK : Macmillan Education, 2011)
Accompanying CD-ROM at the back of the book.
Includes bibliographical references and index.
Keywords: Learning, Psychology of; English language -- Study and teaching -- Textbooks